2020
DOI: 10.1111/ssqu.12782
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting National Medal Totals at the Summer Olympic Games Reconsidered

Abstract: Objective This article aims at explaining national medal totals at the 1992–2016 Summer Olympic Games (n = 1,289 observations) and forecasting them in 2016 (based on 1992–2012 data) and 2020 with a set of variables similar to previous studies, as well as a regional (subcontinents) variable not tested previously in the literature in English. Method Econometric testing not only resorts to a Tobit model as usual but also to a Hurdle model. Results Most variables have a significant impact on national team medal to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 23 publications
0
33
1
Order By: Relevance
“…Based on their review of the literature at the macro-level, the authors noted that more than 50% of the determinants of success are macro-level variables that are beyond the control of politicians, such as population, gross domestic product (GDP) per capita and climatic circumstances. Recent research confirms this in the Summer Olympic Games (Scelles et al 2020), international women's football (Jacobs 2014) and men's football Andreff 2019). De Bosscher et al (2006) also highlighted that the mesolevel contains factors fully or partially determined by sports policies and politics.…”
Section: Introductionmentioning
confidence: 76%
“…Based on their review of the literature at the macro-level, the authors noted that more than 50% of the determinants of success are macro-level variables that are beyond the control of politicians, such as population, gross domestic product (GDP) per capita and climatic circumstances. Recent research confirms this in the Summer Olympic Games (Scelles et al 2020), international women's football (Jacobs 2014) and men's football Andreff 2019). De Bosscher et al (2006) also highlighted that the mesolevel contains factors fully or partially determined by sports policies and politics.…”
Section: Introductionmentioning
confidence: 76%
“…However, there are also other studies that, although they do not focus primarily on property rights and economic systems, present results that support Shughart and Tollison (1993), Bernard andBusse (2004), andCampbell et al (2005). See, for example, Hoffman et al (2002Hoffman et al ( , 2004, Johnson andAli (2004), andScelles et al (2020). Separately, see Li et al (2009) for a discussion of the Chinese government's role in that country's Olympic medal successes.…”
Section: Discussionmentioning
confidence: 93%
“…Since this seminal publication, a number of studies estimated Tobit models to predict the number of medals won by each country (Andreff, Andreff, and Poupaux, 2008;Forrest, Sanz, and Tena, 2010). 3 Similarly, Scelles et al (2020) further investigated the methodological approach and demonstrated that Hurdle models perform better than Tobit models in predicting team medals. These authors concluded that both models should be used for forecasting purposes.…”
Section: Literature Reviewmentioning
confidence: 99%